2021
DOI: 10.26466/opus.877220
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Teachers' Perceptions of Organizational Justice and Authentic Leadership and Their Levels of Organizational Happiness

Abstract: The purpose of this study is to determine the relationship between teachers' perceptions of organizational justice and authentic leadership and their organizational happiness levels. The research was carried out in survey model. The population of the study consists of teachers working in public schools in Elazig province center in the 2019-2020 academic year. The sample of the research was determined by quota sampling method, and the research was carried out by analyzing the data obtained from 436 teachers ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Nonetheless, nurses may develop an external locus of control due to influences such as those from patients, coworkers, physicians, and the physical setting of their jobs. This is comparable to Cheung's et al (2020) study, which demonstrated that COVID-19 specific healthcare simulation training programs enhanced the personal strengths of healthcare workers to a significant extent (Demir and Zincirli, 2021). These strengths included assertiveness, mental preparedness, self-efficacy, and an internal locus of control.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Nonetheless, nurses may develop an external locus of control due to influences such as those from patients, coworkers, physicians, and the physical setting of their jobs. This is comparable to Cheung's et al (2020) study, which demonstrated that COVID-19 specific healthcare simulation training programs enhanced the personal strengths of healthcare workers to a significant extent (Demir and Zincirli, 2021). These strengths included assertiveness, mental preparedness, self-efficacy, and an internal locus of control.…”
Section: Discussionsupporting
confidence: 71%
“…This suggests that those who have been through a divorce or separation tend to be more open, honest, and selfaware than their married or single peers. However, the findings of Demir and Zincirli's (2021) study indicated that the participants' opinions of authentic leadership did not vary, regardless of whether the participants were married or single at the time of the investigation. From what could be gleaned from the existing literature, it appears that identical findings were obtained by other researchers (Kocak and Ohsan, 2022;Başaran and Kiral, 2020).…”
Section: Discussionmentioning
confidence: 76%
“…OJ comprehends employees’ perceptions of fair treatment by the organization, including ethical, accurate, consistent and standardized policies and practices (Demir and Zincirli, 2021; Roberson and Colquitt, 2005). Colquitt (2001) has proposed four dimensions of justice: distributive justice (fair outcomes), procedural justice (employee voice and adherence to procedural rules), informational justice (reasonable and timely explanations) and interpersonal justice (polite and respectful treatment) (Workman-Stark, 2021).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%